Rotational energy distributions of benzene liberated from aqueous liquid microjets: A comparison between evaporation and infrared desorption - Maselli, O.; Gascooke, J.; Kobelt, S.; Metha, G.; Buntine, Mark (CSIRO Publishing, 2006)
We have measured the rotational energy distribution of benzene molecules both evaporated and desorbed by an IR laser from a liquid microjet. Analysis of the 6(0)(1) vibronic band of benzene has shown that the benzene molecules evaporating from the liquid microjet surface have a rotational temperature of 157 +/- 7 K. In contrast, the rotational temperature of benzene molecules desorbed from the liquid microjet by a 1.9 mu m laser pulse is 82 +/- 5 K. However, in both cases careful inspection of the spectral profiles shows that the experimental rotational distributions are non-Boltzmann, displaying an underpopulation of high rotational states and a relative overpopulation of the low rotational states. The non-equilibrium evaporation and desorption spectral profiles are consistent with a model that involves transfer of internal energy into translation upon liberation from the condensed phase.